2014
DOI: 10.1530/erc-13-0473
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning therapy for thyroid cancer: new insights on established medications

Abstract: Repositioning of established non-cancer pharmacotherapeutic agents with well-known activity and side-effect profiles is a promising avenue for the development of new treatment modalities for multiple cancer types. We have analyzed some of the medications with mechanism of action that may have relevance to thyroid cancer (TC). Experimental in vitro and in vivo evidences, as well as results of clinical studies, have indicated that molecular targets for medications currently available for the treatment of mood di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…The administration of CB2 agonist JWH133 (daily intratumoral injection of 50 µg/mL for 3 weeks) led to a considerable regression of thyroid tumors generated in nude mice by inoculation of the TC cells ARO/CB2 [106]. Endocannabinoids were effective against cancer cells with activated BRAF/ERK and/or TrkA signaling, suggesting their potential utility for the treatment of BRAF-positive papillary thyroid carcinoma (PTC) and TrkA-positive medullary thyroid cancer [107].…”
Section: Pancreatic and Thyroid Cancersmentioning
confidence: 99%
“…The administration of CB2 agonist JWH133 (daily intratumoral injection of 50 µg/mL for 3 weeks) led to a considerable regression of thyroid tumors generated in nude mice by inoculation of the TC cells ARO/CB2 [106]. Endocannabinoids were effective against cancer cells with activated BRAF/ERK and/or TrkA signaling, suggesting their potential utility for the treatment of BRAF-positive papillary thyroid carcinoma (PTC) and TrkA-positive medullary thyroid cancer [107].…”
Section: Pancreatic and Thyroid Cancersmentioning
confidence: 99%
“…Indications for both dronabinol and nabilone include the treatment of recalcitrant nausea and vomiting following chemotherapy in cancer patients. Dronabinol is also approved as an appetite stimulant in diseases such as AIDS which result in severe weight loss . (Table )…”
Section: Current Cannabinoid‐based Therapiesmentioning
confidence: 99%
“…Although presently absent within otolaryngology literature, there is encouraging in vitro and in vivo data demonstrating significant antineoplastic potential of the ESS within a wide variety of cancer models . The ENT‐related tumors with data demonstrating the potential antineoplastic activity of cannabinoids include oropharyngeal and tongue cancer, thyroid cancer, lymphoma, basal cell, squamous cell, and melanoma . Using a mouse model, Shi et al demonstrated a strong antitumoral effect on anaplastic thyroid cancer cell lines.…”
Section: Potential Therapies For the Otolaryngic Patientmentioning
confidence: 99%
See 2 more Smart Citations